The Comparative Analysis of Two RT-qPCR Kits for Detecting SARS-CoV-2 Reveals a Higher Risk of False-Negative Diagnosis in Samples with High Quantification Cycles for Viral and Internal Genes - Roberto Luraschi; Carlos Barrera-Avalos; Eva Vallejos-Vidal; Javiera Alarcón; Andrea Mella-Torres; Felipe Hernández; Ailen Inostroza-Molina; Daniel Valdés; Mónica Imarai; Claudio Acuña-Castillo; Felipe E. Reyes-López; Ana María Sandino (Canadian Journal of Infectious Diseases and Medical Microbiology)
The early detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) using the real-time quantitative polymerase chain reaction (RT-qPCR) as a gold-standard molecular tool has allowed to test and trace the viral spread and the isolation of COVID-19-infected patients. The detection capacity of viral and internal genes is an essential parameter to consider and analyze during the assay. In this study, we analyze the performance of the two commercial RT-qPCR kits used in Chile, TaqMan™ 2019-nCoV Control Kit v1 (Thermo Fisher) and MaxCov19 (TAAG Genetics), for the COVID-19 diagnosis from nasopharyngeal swab samples (NPSs). Our results show a lower sensitivity of the TAAG kit compared to the Thermo Fisher kit, even in the detection of SARS-CoV-2 mutations associated with its variants. This study reinforces the relevance of evaluating the performance of RT-qPCR kits before being used massively since those with lower sensitivity can generate false negatives and produce outbreaks of local infections.